Modification of solidification microstructure in hypo- and hyper-eutectic Al–Si alloys under high-intensity ultrasonic irradiation - Amit Das (Journal of Alloys and Compounds, 2015)
In this study, the effect of ultrasonic irradiation is investigated on the solidification microstructure of hypo- and hyper-eutectic Al–Si alloys. Significant grain refinement accompanying dendrite to equiaxed transition was observed for the primary solid in both the alloys. Analysis of cooling curves suggest that enhanced heterogeneous nucleation under ultrasonication is responsible for the refinement of the microstructure. In the region of the ultrasonic energy transfer, strong fluid flow effect resulted in predominant spheroidisation of the eutectic-Si plates.